MODIFIED FIXED-ANGLE STRUT-AND-TIE MODEL FOR HIGH STRENGTH REINFORCED CONCRETE BEAMS - Tavio Tavio (Institut Teknologi Sepuluh Nopember, 2009)
Nonlinear finite element analysis was applied to various reinforced concrete beams using a set of constitutive models established in the modified fixed-angle softened-truss model (MFA-STM). The model was implemented by modifying the general-purpose program FEAPpv. The model can take account of the six important characteristics of cracked reinforced concrete: (1) the softening effect of concrete in tension-compression; (2) the tension-stiffening effect of concrete in tension; (3) the average stress-strain curve of steel bars embedded in concrete; (4) the shear modulus of concrete; (5) the aggregate interlock; and (6) dowel action. The comparison shows the aggregate interlock and dowel action can reduce the overestimation of the shear capacity of high strength reinforced beam, especially the high strength reinforced deep beam without web reinforcement. Moreover, the model is suitable for being implemented numerical procedures due its simplicity.